Design Analysis and Experiment of Lower Limb Power Exoskeleton - Wei Ning; Gang Li; Zhendong Song; Wei Chen; Tong Wu (Jixie chuandong)
Abstract In order to effectively solve the motor dysfunction of lower limbs in the elderly caused by the degeneration of lower limb muscle function and stroke hemiplegia， the importance of rehabilitation exercise for the recovery of lower extremity dysfunction patients is analyzed from the perspective of rehabilitation medicine. Combining with the physiological structure of human body， a human musculoskeletal model is established and the musculoskeletal simulation analysis is carried out. In order to accurately judge the motion intention of patients， three kinds of special sensors for exoskeleton are designed. On this basis， a force sensing joint structure scheme is proposed， and the overall structure of the lower limb power exoskeleton is designed. The human-machine coupling kinematics simulation analysis is carried out. On the basis of structure design， the hardware and electrical system of lower limb exoskeleton are designed. In order to verify the correctness of theoretical research， the exoskeleton prototype is processed and related experiments are carried out. The experimental results show that the special exoskeleton sensor designed can accurately acquire the corresponding signals， and the assistant joints can provide greater joint assistance. The designed lower limb power exoskeleton can accurately judge the motion intention of patients， and can walk steadily and safely on the ground and on the slope for a long time.